Understanding pastoral counseling - Maynard, Elizabeth A.; Snodgrass, Jill Lynnae (Springer Publishing Company, 2015)
What are the roles, functions, and identities of pastoral counselors today? What paradigms shape their understandings of the needs of others? How can pastoral counselors serve the needs of diverse individuals in both religious and secular environments? This foundational text reflects the continued and unfolding work of pastoral counseling in both clinical and traditional ministry settings. It addresses key issues in the history, current practices, and future directions in pastoral counseling and its place among allied helping professions. Written to incorporate current changes in the roles of pastoral counselors and models of training beyond the traditional seminary, the book builds on themes of pastoral counseling as a distinct way of being in the world, understanding client concerns and experiences, and intervening to promote the health and growth of clients.